The Influence of Social Media in Increasing the Number of New Students at the Private Islamic Senior High School (MAS) Aisyiyah Medan - Nur Jannah; Dewi Wulandari; Cici Handayani (SEAN Institute, 2025)
This study aims to examine the influence of social media in increasing the number of new students at the Private Madrasah Aliyah (MAS) Aisyiyah Medan. Social media is considered an effective tool in promoting educational institutions, given its increasingly important role in everyday life, especially for the younger generation. This study uses a quantitative method with multiple linear regression analysis to measure the relationship between social media use and the number of new student registrants. The results of the study indicate that social media has a significant positive effect on increasing the number of new students at MAS Aisyiyah Medan. The t-test and F-test prove that the use of social media overall has a significant impact on attracting prospective students, with a regression coefficient of 0.418 and a significance value of 0.000 indicating a strong influence. In addition, the majority of students who registered were 14 years old, with 56% of them being female students. These findings indicate that social media is an effective marketing tool to reach a wider and more diverse audience. This study contributes to the development of social media-based educational marketing strategies in Indonesia, especially for private educational institutions.